If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6k + 6 + -3k + 8 = 0 Reorder the terms: 6 + 8 + -6k + -3k = 0 Combine like terms: 6 + 8 = 14 14 + -6k + -3k = 0 Combine like terms: -6k + -3k = -9k 14 + -9k = 0 Solving 14 + -9k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -9k = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -9k = 0 + -14 -9k = 0 + -14 Combine like terms: 0 + -14 = -14 -9k = -14 Divide each side by '-9'. k = 1.555555556 Simplifying k = 1.555555556
| 3x-y=31 | | 5.7n+4.1=2.96 | | Y^2-9=11x | | (15)29-n=225 | | 15(29-n)=225 | | 15(n-29)=225 | | s=1/8(80) | | s+1/8=80 | | 80s=1/8 | | 61/2x33/13 | | 102+x=(4x+6) | | 2s+4=5(-4-2s) | | (x^2-3x+2)(x^2+3x-8)=24 | | 3+3*6-2=0 | | 3-2(b-2)=2-7b | | 12h=4(2h-5) | | 5x+8y-9x= | | x^3-x^2-11x=0 | | 4(-6)-5(2)/2(2) | | x+x(0.13)=7091.88 | | Y-4X-1=6X+6X^2 | | 6t+4=3t-2 | | -t=9(t-10) | | 2x^2+2=-13 | | 3m*3n= | | 2x^2+2=-5 | | 2/3=n+2/21 | | 29x+30x=28x+38 | | 7(2e-1)-3=6+6e | | ln(x)+ln(7)=2*ln(x) | | 5x-2)^2/(x-3)=(4-20x+25x^2)/(24-11x+x^2) | | y=11X^2+4-1 |